Postmodern street-art protest: main forms and features - Клюєнко E. О. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
The article is devoted to the analysis of pecularaties of postmodern character of political protest. The political street-art protest has been analyzed as the result of the newest influenses of postmodern culture on politics. The main forms of street-art protest have been defined and the staginess, spectacular characteristics revealed.